2001
DOI: 10.1046/j.1525-1470.2001.018001009.x
|View full text |Cite
|
Sign up to set email alerts
|

Louse Comb Versus Direct Visual Examination for the Diagnosis of Head Louse Infestations

Abstract: The techniques used for diagnosis of head louse (Pediculosis capitis) infestation are a source of controversy. Most epidemiologic and diagnostic studies have been done using direct visual examination. The main objective of this study is to compare the efficacy of direct visual examination versus the louse comb method. The hair of each child was examined twice; one team used a screening stick and another team used a louse comb. Seventy-nine boys and 201 girls, 7-10 years old were examined. Examination with a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 5 publications
0
64
0
3
Order By: Relevance
“…Thereafter, the same investigator re-examined the participant's entire scalp by wet combing (using a commercial head-lice comb) -the most sensitive method for detecting head lice 5,12,13,18 . The hair was moistened and a commercial conditioner applied.…”
Section: Methodsmentioning
confidence: 99%
“…Thereafter, the same investigator re-examined the participant's entire scalp by wet combing (using a commercial head-lice comb) -the most sensitive method for detecting head lice 5,12,13,18 . The hair was moistened and a commercial conditioner applied.…”
Section: Methodsmentioning
confidence: 99%
“…This time was set based on Mumcuoglu et al, 6 who showed that the average time until detection of the first (mobile) louse by direct visual examination was 116 seconds. Based on the results obtained by Williams et al 14 special attention was put on the number and position of nits in relation to the scalp as indicators of parasitism intensity.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have revealed that diagnosis of infestation by using a louse comb is quicker and more efficient. 22 Some experts have suggested using a lubricant (water, oil, or conditioner) to "slow down" the movement of lice and eliminate the possibility of static electricity. 23 The tiny eggs may be easier to spot, especially at the nape of the neck or behind the ears, within 1 cm of the scalp.…”
Section: Diagnosismentioning
confidence: 99%